2020
DOI: 10.1073/pnas.1917204117
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying snowfall from orographic cloud seeding

Abstract: Climate change and population growth have increased demand for water in arid regions. For over half a century, cloud seeding has been evaluated as a technology to increase water supply; statistical approaches have compared seeded to nonseeded events through precipitation gauge analyses. Here, a physically based approach to quantify snowfall from cloud seeding in mountain cloud systems is presented. Areas of precipitation unambiguously attributed to cloud seeding are isolated from natural precipitation (<1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 14 publications
(20 reference statements)
0
32
0
1
Order By: Relevance
“…Comparison to tower and sounding data have indicated that differences in temperatures are below 1.58C (Friedrich et al 2012;Bianco et al 2017). The vertical resolution of the retrieved profiles ranged from 50 m between the surface and 0.5 km AGL; 100 m between 0.5 and 2 km AGL; and 250 m between 2 and 10 km AGL.…”
Section: B Defining Thermodynamics and Dynamics Through Radiometer And Rawinsondesmentioning
confidence: 97%
See 1 more Smart Citation
“…Comparison to tower and sounding data have indicated that differences in temperatures are below 1.58C (Friedrich et al 2012;Bianco et al 2017). The vertical resolution of the retrieved profiles ranged from 50 m between the surface and 0.5 km AGL; 100 m between 0.5 and 2 km AGL; and 250 m between 2 and 10 km AGL.…”
Section: B Defining Thermodynamics and Dynamics Through Radiometer And Rawinsondesmentioning
confidence: 97%
“…The authors acknowledge that the maximum Z e value between the surface and 4 km MSL does not necessarily represent the snow hitting the surface, and that snow may continue to grow or sublimate in the atmosphere below and is a source of uncertainty in our analysis. Additionally, conversion of Z e to snowfall rates (S) depends on the snow characteristics and a large variety of Z e -S relationships and strategies to derive radar-based snowfall rates exist (e.g., Puhakka 1975;Wolfe and Snider 2012;Friedrich et al 2020). Instead of using S, we used Z e as a relative metric to compare snowfall in each pathway as if the same Z e -S relationship was applied to all cases.…”
Section: Precipitation Observing Systemmentioning
confidence: 99%
“…The cloud could respond to seeding very differently if the AgI particles are released from an aircraft. The recently completed Seeded and Natural Orographic Wintertime Clouds: The Idaho Experiment (SNOWIE) field campaign collected a wealth of in situ and remote sensing measurements and observed clear seeding signals in clouds treated by aircraft seeding (French et al 2018;Tessendorf et al 2019;Friedrich et al 2020), which provides great opportunities to validate and improve our model in the near future. The possible indication of seedability level by the novel h-LWP parameter will be tested in the SNOWIE cases.…”
Section: Diffusional Growth Of Liquidmentioning
confidence: 99%
“…When seeding materials are injected into the cloud top, the simplest and easiest‐to‐observe cloud‐seeding feature is the glaciation and collapse of the cloud top (Langmuir, 1961), which indicates that the cloud‐seeding materials have altered the microphysical characteristics and structure of the cloud. Radar is a common tool to identify microphysical changes in cloud properties resulting from cloud seeding (French et al., 2018; Friedrich et al., 2020; Geerts et al., 2010; Hobbs et al., 1981; Pokharel, Geerts, Jing, Friedrich, Aikins, et al., 2014). Based on measurements from ground‐based X‐band radars, an airborne W‐band cloud radar and in situ physical cloud probes, French et al.…”
Section: Introductionmentioning
confidence: 99%
“…Friedrich et al. (2020) identified areas of orographic precipitation that were unambiguously generated by cloud seeding through the identification of seeding tracks with enhanced radar reflectivity, which could then be connected to enhanced surface snowfall.…”
Section: Introductionmentioning
confidence: 99%